The Political Economy of Hatred* - Glaeser, Edward L. (Quarterly Journal of Economics, 2005)
What determines the intensity and objects of hatred?Hatred forms when people believe that outgroups are responsible for past and future crimes, but the reality of past crimes has little to do with the level of hatred.Instead, hatred is the result of an equilibrium where politicians supply stories of past atrocities in order to discredit the opposition and consumers listen to them.The supply of hatred is a function of the degree to which minorities gain or lose from particular party platforms, and as such, groups that are particularly poor or rich are likely to be hated.Strong constitutions that limit the policy space and ban specific anti-minority policies will limit hate.The demand for hatred falls if consumers interact regularly with the hated group, unless their interactions are primarily abusive.The power of hatred is so strong that opponents of hatred motivate their supporters by hating the haters.